2023
DOI: 10.3390/ijerph20042963
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Post-Eradication Smallpox Vaccine as an Mpox Vaccine: A Systematic Review with Meta-Analysis

Abstract: According to the World Health Organization, 83,339 laboratory-confirmed cases, including 72 deaths, of mpox (formerly known as monkeypox), have been reported from 110 locations globally as of 20 December 2022, making the disease a public health concern. Most of the cases (56,171, 67.4%) were reported from countries in North America. Limited data on vaccine effectiveness in the current mpox outbreak are available. However, the modified vaccinia virus (smallpox vaccine) has been predicted to prevent or reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A recent meta-analysis evaluated the safety of MVA among vaccinia-naïve versus vaccinia-experienced people and demonstrated higher rates of adverse events in the former [ 37 ]. The prescribing information for MVA (JYNNEOS) summarizes data from 22 studies (7859 individuals) and reports some variability in AEs between vaccine-experienced and naïve individuals, along with similar rates of AEs between healthy individuals and those with HIV or atopic dermatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis evaluated the safety of MVA among vaccinia-naïve versus vaccinia-experienced people and demonstrated higher rates of adverse events in the former [ 37 ]. The prescribing information for MVA (JYNNEOS) summarizes data from 22 studies (7859 individuals) and reports some variability in AEs between vaccine-experienced and naïve individuals, along with similar rates of AEs between healthy individuals and those with HIV or atopic dermatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of the vaccine against mpox has not been assessed in clinical trials, real-world studies have shown good effectiveness [13,14,20,21]. A recent study from Israel evaluating 1037 male individuals who completed only the first subcutaneous dose of the vaccine and were followed up for at least 90 days estimated that the adjusted vaccine effectiveness in preventing infection was 86% (95% confidence interval 59-95%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…The earlier vaccinia virus vaccination administered against smallpox provided crossimmunity to the mpox virus as both viruses are closely related to Orthopoxviruses [13,14]. Discontinuation of routine smallpox vaccination following smallpox eradication in the early 1980s and thus waning immunity with no immunity coverage in the population <40 years of age has probably been an important risk factor for the current emergence of mpox as a public health thread [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, a total of 212 participants were included out of 219, and the majority of participants provided correct responses about the type of microorganisms that cause human Mpox infection, which is a virus, these results were comparable to a previous study that was conducted in Indonesia. This study aimed to determine general practitioners' knowledge regarding Mpox, and majority of participants (96.6%) knew Mpox is a virus [ 14 ]. In the current study, majority of participants were aware of the low prevalence of Mpox in Saudi Arabia, but only small proportion identified the correct number of cases in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%